Future of European Security Policies: Is Geopolitical Europe Possible? - Ahmet K. Han; Çiğdem Üstün (Ankara Avrupa Çalışmaları Dergisi)
Since the aftermath of World War II, the pursuit of European autonomy in ensuring its security began with the 1950s French proposal for a pan-European defense force, though never realized. The Lisbon Treaty facilitated Union representation as a legal entity and introduced Permanent Structured Cooperation (PESCO) to deepen defense ties. Geopolitical ambitions increased with von Der Leyen's 2019 call for a Geopolitical Commission, preceding the Russia-Ukraine conflict. Global geopolitical shifts amplify the need for a robust European role. However, EU's historical struggle in forging a strong security policy fuels skepticism. This study assesses the EU's foreign policy in the Mediterranean and Black Sea amidst regional turmoil, employing a neo-classical realist lens and a global perspective.